Children’s Preference for Causal Information in Storybooks - Shavlik, Margaret; Bauer, Jessie Raye; Booth, Amy E. (Frontiers in Psychology, 2020)
Fostering early literacy depends in part on engaging and inspiring children’s early interest in reading. Enriching the causal content of children’s books may be one way to do so, as causal information has been empirically shown to capture children’s attention. To more directly test whether children’s book preferences might be driven by causal content, we created pairs of expository books closely matched for content and complexity, but with differing amounts of causal information embedded therein. Three- and 4-year-old participants (n = 48) were read both books and their interests and preferences were evaluated. When asked to choose, children preferred the highly causal over the minimally causal books. Results are discussed in terms of broader implications for creating books that optimally engage young children, as well as guiding book selections parents and educators make in their endeavors to promote interest in reading and early literacy.